Prospective evaluation of small bowel preparation with bisacodyl and sodium phosphate for capsule endoscopy - Franke, Andreas; Hummel, Frank; Knebel, Phillip; Antoni, Christoph Helmer; Böcker, Ulrich; Singer, Manfred V.; Löhr, J.-Matthias (World journal of gastroenterology, 2008)
AIM: To determine the effect of Prepacol®, a combination of sodium phosphate and bisacodyl, on transit and quality of capsule endoscopy (CE)., METHODS: Fivety two consecutive patients were included in this prospective study. CE was performed following a 12 h fasting period. Twenty six patients were randomized for additional preparation with Prepacol®. The quality of CE was assessed separately for the proximal and the distal small bowel by 3 experienced endoscopists on the basis of a graduation which was initially developed with 20 previous CE., RESULTS: Preparation with Prepacol® accelerated small bowel transit time (262 ± 55 min vs 287 ± 97 min), but had no effect on the quality of CE. Visibility was significantly reduced in the distal compared to the proximal small bowel., CONCLUSION: The significantly reduced visibility of CE in the distal small bowel allocates the need for a good preparation. Since Prepacol® has no beneficial effect on CE the modality of preparation and the ideal time of application remains unclear. Further standardized examinations are necessary to identify sufficient preparation procedures and to determine the impact of the volume of the preparation solution.
Gesehen am 15.03.2022